Leadership Development in the 21st Century: A Modern Approach to Talent Cultivation - Nasution, Rizki Alfadillah; Suprianto, Ghalib; Ahsani, Riska Fii (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research investigates the interplay between leadership development, modern approaches, and talent cultivation within the organizational context of PT. Alsindo Pekanbaru. Utilizing a quantitative research design and Structural Equation Modeling (SEM) analysis with SmartPLS software, data were collected from 80 employees using random sampling techniques. The results reveal significant direct effects of Leadership Development and Modern Approach on Talent Cultivation, indicating their pivotal roles in shaping talent development initiatives within the organization. Additionally, indirect effects analysis demonstrates that Leadership Development and Modern Approach influence Talent Cultivation through the mediator of 21st Century Approach, highlighting the importance of aligning organizational strategies with contemporary paradigms. These findings underscore the significance of investing in leadership development tailored to meet the demands of the modern business landscape and embracing modern approaches to foster talent cultivation effectively. Such insights are invaluable for organizations like PT. Alsindo Pekanbaru in enhancing organizational agility, innovation, and long-term competitiveness in the ever-evolving marketplace.